2011
DOI: 10.1029/2011jd015830
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations of the transport of black carbon and carbon monoxide from the Asian continent to the western Pacific in the boundary layer

Abstract: [1] Continuous in situ measurements of the mass concentration of black carbon (BC) aerosols and mixing ratio of carbon monoxide (CO) were made at Cape Hedo on Okinawa Island, Japan, a remote site located in the East China Sea, from March 2008 to May 2009. For the first time, we show temporal variations of BC and CO at Hedo in Asian outflows throughout the year. Annual average concentrations of BC and CO were 0.29 mg m −3 and 150 ppbv, respectively. The origins of the observed air masses were determined by usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 64 publications
(148 reference statements)
3
59
0
Order By: Relevance
“…5a). This is within the range of 1.4-5.4 ng m −3 ppb −1 obtained in winter at the Hedo site (Okinawa Island, Japan) due to long-range transport of pollution plumes from East Asia (Verma et al, 2011), but on average it is lower than the values reported for industrial and urban regions of East Asia and North America (Table 3). Most likely in wintertime scavenging by ice crystal precipitation (Cozic et al, 2007) and dry deposition of EC has resulted in decreasing EC / CO ratios during the air mass transport from the pollution sources to the ZOTTO site.…”
Section: Characterisation Of Polluted Airmentioning
confidence: 53%
See 1 more Smart Citation
“…5a). This is within the range of 1.4-5.4 ng m −3 ppb −1 obtained in winter at the Hedo site (Okinawa Island, Japan) due to long-range transport of pollution plumes from East Asia (Verma et al, 2011), but on average it is lower than the values reported for industrial and urban regions of East Asia and North America (Table 3). Most likely in wintertime scavenging by ice crystal precipitation (Cozic et al, 2007) and dry deposition of EC has resulted in decreasing EC / CO ratios during the air mass transport from the pollution sources to the ZOTTO site.…”
Section: Characterisation Of Polluted Airmentioning
confidence: 53%
“…The strength of the correlation between EC and CO strongly depends on the meteorological conditions. Wet deposition can affect aged EC Verma et al, 2011;Kanaya et al, 2016) but not CO, while CO can be removed from the atmosphere by oxidation with OH radicals (Hamilton et al, 2014). In addition, as noted above, CO can be produced from the oxidation of methane and non- Meadow-grass straw, wheat straw 10.9 ± 1.5 (F) 5.4 ± 4.3 (F) Dhammapala et al (2007b) a TOT (TOR) -thermal-optical transmittance (reflectance).…”
Section: Characterisation Of Polluted Airmentioning
confidence: 99%
“…The overall slope ( BC e / CO) for all polluted periods in winter is 9.3 ng m −3 ppb −1 with R 2 = 0.55, which is higher than values normally found at rural sites (Kondo et al, 2006;Wang et al, 2011) and even at the higher end of the literature range for cities in Asia (Verma et al, 2011;Wang et al, 2011). If we assume that the pollution at ZOTTO mainly comes from anthropogenic emissions in Siberian cities, our data suggests that those emissions have a higher BC / CO emission ratio than known from other cities in the literature.…”
Section: Polluted Winter Airmentioning
confidence: 89%
“…We discuss the seasonal changes of these components and transformations of organic aerosol (OA) during the longrange transport of Asian aerosols. Many studies related to the atmospheric chemistry have been conducted at Cape Hedo (Sato et al, 2009;Wang et al, 2009;Zhang et al, 2003;Jaffe et al, 2005;Verma et al, 2011;Lun et al, 2009;Yamamoto and Kawamura, 2011;Ueda et al, 2011;Arakaki et al, 2006;Handa et al, 2010;Mochida et al, 2010). However, no studies were conducted for a long-term measurement of OC, EC, WSOC, WSTN, WSON and major ions in atmospheric aerosols from Cape Hedo, Okinawa Island.…”
Section: Introductionmentioning
confidence: 99%